A contemporary history of circus arts in Buenos Aires, Argentina: the post-dictatorial resurgence and revaluation of circus as a popular art - Infantino, Julieta Lorena (2015)
The purpose of this paper is to study the process of resurgence and redefinition of popular practices promoted in the city ofBuenos Aires,Argentina, in post- dictatorial years, through the case of circus arts. Therefore, I will first present some historical data that will enable understanding of the transitional legitimacy given to circus in the late nineteenth century and synthetically introduce the social processes that led circus into a process of retraction. Then I will focus on the social actors who recovered these artistic languages in the post- dictatorship, contextualizing their practices with the socio-political changes of the time. The analyses will center on the way in which young artists recovered certain elements of the past to give sense to the present activity and innovated in the artistic practice, legitimizing their practices and challenging their recognition.